Development and validation of the Learning Disabilities Needs Assessment Tool (LDNAT), a HoNOS‐based needs assessment tool for use with people with intellectual disability. Issue 12 (11th October 2016) - Painter, J.; Trevithick, L.; Hastings, R. P.; Ingham, B.; Roy, A.
Abstract: Background: In meeting the needs of individuals with intellectual disabilities (ID) who access health services, a brief, holistic assessment of need is useful. This study outlines the development and testing of the Learning Disabilities Needs Assessment Tool (LDNAT), a tool intended for this purpose. Method: An existing mental health (MH) tool was extended by a multidisciplinary group of ID practitioners. Additional scales were drafted to capture needs across six ID treatment domains that the group identified. LDNAT ratings were analysed for the following: item redundancy, relevance, construct validity and internal consistency ( n  = 1692); test–retest reliability ( n  = 27); and concurrent validity ( n  = 160). Results: All LDNAT scales were deemed clinically relevant with little redundancy apparent. Principal component analysis indicated three components (developmental needs, challenging behaviour, MH and well‐being). Internal consistency was good (Cronbach alpha 0.80). Individual item test–retest reliability was substantial‐near perfect for 20 scales and slight‐fair for three scales. Overall reliability was near perfect (intra‐class correlation = 0.91). There were significant associations with five of six condition‐specific measures, i.e. the Waisman Activities of Daily Living Scale (general ability/disability), Threshold Assessment Grid (risk), Behaviour Problems Inventory for Individuals with Intellectual Disabilities‐Short Form (challenging behaviour) Social Communication Questionnaire (autism) and a bespoke physical health questionnaire. Additionally, the statistically significant correlations between these tools and the LDNAT components made sense clinically. There were no statistically significant correlations with the Psychiatric Assessment Schedules for Adults with Developmental Disabilities (a measure of MH symptoms in people with ID). Conclusions: The LDNAT had clinically utility when rating the needs of people with ID prior to condition‐specific assessment(s). Analyses of internal and external validity were promising. Further evaluation of its sensitivity to changes in needs is now required.